Percutaneous treatment of a CTO in an anomalous right coronary artery: A rupture paved the way for new insights - Cocco, Nino; Madonna, Rosalinda; Cammalleri, Valeria; Cocco, Giulio; De Stefano, Domenico; Ricciardi, Danilo; Grigioni, Francesco; Ussia, Gian Paolo (Frontiers in Cardiovascular Medicine, 2022)
Anomalous aortic origin of a coronary artery (AAOCA) from the opposite sinus with interarterial course has been associated with an increased risk of myocardial ischemia and sudden death. As the exact pathophysiology of AAOCA is not well understood, the clinical management is not well defined. With the increased use of non-invasive imaging, the diagnosis of AAOCA is increasing and the association of anomalous origin and atherosclerotic disease will become a new topic. We report a rare case of AAOCA chronic total occlusion (CTO). A 40-year-old Caucasian male was referred for invasive coronary angiography (ICA) due to typical chest pain and positive myocardial scintigraphy. ICA demonstrated CTO of an anomalous right coronary artery (ARCA) originating from the left side of the ascending aorta with interarterial course and no lesion in the left coronary artery. During the procedure unexpected rupture of the coronary artery occurred after dilatation with a small balloon at low pressure. Coronary artery perforations are rare but life-threatening procedural complications that are usually caused by anatomical and procedural factors that predispose to this dramatic event. After literature review for the first time we performed an estimation of the risk of sudden death specific for ARCA and issue a warning on the risk of complication during complex percutaneous coronary intervention of these arteries. Finally, we reconsider the pathophysiology of the anomaly in a way that could change the approach to the disease. Based on this complication, we speculate that the wall of the artery could be fragile due to histopathological alterations, which could have a role in the pathophysiology of coronary malignancy.